Prevention and Treatment of Postoperative Pain after Lumbar Spine Procedures: A Systematic Review. Issue 7 (25th March 2018) - Terracina, Sergio; Robba, Chiara; Prete, Anna; Sergi, Paola G.; Bilotta, Federico
Abstract: Background and Objective: In the past 2 decades, in developed countries, spine procedures (surgical and percutaneous) had the highest absolute increase in case volume trend. The optimal approach to prevent and treat postoperative pain is continuously evolving. This systematic literature review presents evidence on safety and efficacy of pharmacological and nonpharmacological therapies to prevent and treat postoperative pain after lumbar spine procedures. Databases and Data Treatment: Publications listed in PUBMED and EMBASE were considered to identify randomized clinical trials suitable for inclusion in this systematic review. Key words for literature search were selected, with authors' agreement, using the PICOS approach (participants, interventions, comparisons, outcomes, and study design). Results: Fifty‐nine randomized clinical trials (involving a total of 4, 238 patients, with ages ranging from 18 to 86 years) published between January 2012 and September 2017 were retrieved. Data are presented according to the timing of therapy administration. Conclusion and Recommendations: Clinical evidence on perioperative pain management in patients undergoing spine procedures have significantly evolved after the review published in 2012. The aim of this systematic review was to report the latest evidence published. These include the preoperative use of dexamethasone, which was shown to be able to reduce pain at mobilization but not to reduce pain at rest or total morphine consumption; the use of gabapentinoids as part of a multimodal analgesic approach; and the safety and effectiveness of the intraoperative use of ketamine, dexketoprofen, and tramadol. Finally, electrical nerve stimulation is gaining interest and is potentially suitable for clinical needs.